2019
DOI: 10.1093/jac/dkz217
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of dolutegravir: influence of drug–drug interactions in a real-life setting

Abstract: Objectives Dolutegravir is widely prescribed owing to its potent antiviral activity, high genetic barrier and good tolerability. The aim of this study was to characterize dolutegravir’s pharmacokinetic profile and variability in a real-life setting and to identify individual factors and co-medications affecting dolutegravir disposition. Methods A population pharmacokinetic model was developed using NONMEM®. Relevant demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…Concerning DTG pharmacokinetics, the median AUC 0–24 was 56 613 ng.h/mL [47 805–64 496], median C min 1372 ng/mL [1039–1679], and median C max 3533 ng/mL [3189–3846]. Body weight at week 48 significantly influenced DTG AUC 0–24 ( P = .02), as previously reported 27,30 …”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Concerning DTG pharmacokinetics, the median AUC 0–24 was 56 613 ng.h/mL [47 805–64 496], median C min 1372 ng/mL [1039–1679], and median C max 3533 ng/mL [3189–3846]. Body weight at week 48 significantly influenced DTG AUC 0–24 ( P = .02), as previously reported 27,30 …”
Section: Resultssupporting
confidence: 75%
“…This result is in agreement with other studies. Two studies presented as conference abstracts and evaluating the association between weight gain and DTG pharmacokinetics, specifically plasma ( n = 96, DTG plasma exposure similar to the present study) and hair ( n = 177) concentrations, found no significant association 17–31 . Conversely, some antiretroviral drugs demonstrated a concentration–effect relationship for other adverse events.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations